Radiation Therapy in the Treatment of Brain Tumors in Children (Eurasian Medical Research Periodical, 2022)
Up to 95% of cases of tumors of the central nervous system (CNS) in children are brain tumors. The treatment tactics are determined by their histological variant. If possible, tumors are removed (surgical resection); an important method of treatment in children older than 3 years is radiation therapy; in young children, chemotherapy plays an important role in the treatment of CNS tumors, which allows you to postpone radiation therapy or reduce its dose, and in some cases exclude it altogether. Tumors of the central nervous system (CNS) in children occupy the 2nd place in frequency in the structure of malignant neoplasms of childhood and the 1st place among solid tumors. According to the registers, they account for about 20% of all malignant neoplasms of childhood and are mainly represented by brain tumors (OGM).